2012
DOI: 10.1097/yic.0b013e32834f504f
|View full text |Cite
|
Sign up to set email alerts
|

Obtained effect size as a function of sample size in approved antidepressants

Abstract: The high failure rate of antidepressant trials has spurred exploration of the factors that affect trial sensitivity. In the current analysis, Food and Drug Administration antidepressant drug registration trial data compiled by Turner et al. is extended to include the most recently approved antidepressants. The expanded dataset is examined to further establish the likely population effect size (ES) for monoaminergic antidepressants and to demonstrate the relationship between observed ES and sample size in trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…In summary, given the constraints enforced by the regulators and the inability to control for multiple factors that may influence antidepressant clinical trial outcomes, it is more realistic to set up low expectations. In this context, a recent report by Gibertini et al provides a useful model. These investigators analyzed the data from 81 monoaminergic antidepressant trials conducted in the past three decades, submitted to the FDA for the approval of fifteen antidepressants.…”
Section: The Impact Of Regulatory Decisionsmentioning
confidence: 99%
“…In summary, given the constraints enforced by the regulators and the inability to control for multiple factors that may influence antidepressant clinical trial outcomes, it is more realistic to set up low expectations. In this context, a recent report by Gibertini et al provides a useful model. These investigators analyzed the data from 81 monoaminergic antidepressant trials conducted in the past three decades, submitted to the FDA for the approval of fifteen antidepressants.…”
Section: The Impact Of Regulatory Decisionsmentioning
confidence: 99%
“…[14][15][16] In comparison, the weighted average effect size of 15 antidepressant medications in an analysis of 81 placebo-controlled studies was *0.30. 17 The central nervous system (CNS) effects of flibanserin may not underlie only the efficacy of the drug, but also its safety and tolerability profile. The AE profile of flibanserin reported in this pooled analysis is similar to those of other CNS-acting products [18][19][20][21] and consistent with previous reports for flibanserin.…”
Section: Discussionmentioning
confidence: 99%
“…It is perhaps an underappreciated truism that statistically underpowered studies with small sample sizes (often earlyphase studies) are highly likely to both under-and overestimate treatment effect sizes (2,3). By considering large effects from small studies to be true effects rather than overestimation errors, some researchers have concluded that smaller trials are more advantageous.…”
mentioning
confidence: 99%